Implementation of Digital-Based School Management Systems to Improve Administrative Efficiency in Junior High Schools in East Kalimantan Province (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The rapid development of information technology has influenced nearly every aspect of life, including education. In this context, the digital transformation of school administration has become essential to enhance the quality of services, ensure transparency, and boost operational efficiency. Traditional, manual administrative processes often face challenges such as delayed reporting, inaccurate data entry, and poor information accuracy. The adoption of a digital School Management Information System (SMIS) addresses these issues by enabling automated processes, cloud-based data storage, and real-time access to information. This research investigates the implementation of such systems in schools and evaluates their effect on administrative efficiency. The increasing digital integration in education has driven schools to adopt technology-based management systems as a strategy to improve the effectiveness and efficiency of administrative operations. Employing a descriptive qualitative approach, this study utilizes interviews, observations, and document analysis conducted at three junior high schools in East Kalimantan. Findings indicate that digital systems significantly enhance the speed of data processing, record-keeping, and the transparency of reporting. Nonetheless, issues such as insufficient training and limited technological infrastructure continue to hinder optimal implementation. In summary, while digital school management systems prove effective in streamlining administrative tasks, their success depends on ongoing support through training and sustainable policy frameworks.